Partisipasi Masyarakat Dalam Mengembangkan Subak Lodtunduh Sebagai Daya Tarik Wisata Di Desa Singakerta, Kecamatan Ubud, Gianyar - Nugraha, Alif Rachman; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p16, 2018)
Subak is one of the Balinese cultural heritages, which has been assigned as one of World Cultural Heritage sites by UNESCO. Participation and empowering for local community is very important to occur equalization welfare and suistainable tourism ongoing on Subak Lodtunduh development as a tourist attraction. This research is very important for analyzing the local community participation to tourist attraction development in Subak Lodtunduh focused on development position of Subak Lodtunduh and their local community participation in various aspects. In this research methods used is qualitative research method. Qualitative method is used to reveal the form of local community participation. Qualitative and quantitative data in this research derived from primary and secondary data. Those collected by observation and literature review technique. Primary data explored by indepth interview to several informants that determined by purpossive sampling, then data annalyzed qualitatively to be explained in descriptive method. The result of this research is the form of community participation is limited to external parties such as the opinion by Tosun (1999). There are no real forms of the draft plan or detailed spatial Lodtunduh Subak rice cultivation to be a tourist attraction. The government's role was limited to initiate the Subak Lodtunduh to be more productive in the tourism sector in line with the agricultural sector that has been cultivated local communities Lodtunduh Subak communities.   Keywords : Community Participation, Subak Lodtunduh, Tourist Attraction